Panorama du feu - Gerner, Jochen 1970- (L'Association, 2010)
Le Panorama du Feu is one of the main pieces of Gerner’s solo exhibition presented at the Anne Barrault gallery in September 2009. The artist revisited covers of a large variety of so-called war literature booklets from the 1960s and 1970s. He covered multiple areas in black, highlighted specific words or included pictograms in the old booklets. The author thus highlights the violence of these popular periodicals from the Cold War era. The result is an Oubapian book-object par excellence, an atypical assemblage made up of 50 booklets of 8 pages each gathered in a box. (from publisher)
Hefte sind durchnummeriert von 0-50. - Banderole mit Aufdruck: Guerre
Cet ouvrages a été imprimé à 1000 exemplaire, numérotés de 1 à 1000
Keywords: Gerner, Jochen -- 1970-; Guerre / dans l'art; Périodiques illustrés; Comic